Cell structures, phase morphologies and impact toughness of phenolphthalein poly(ether ether ketone)/epoxy composite foams. Issue 9 (2nd July 2020) - Ding, Yanyu; Zhou, Chaoqian; Ren, Baosheng; Zhang, Aimin; Wang, Guilong
Abstract: Thermoplastic phenolphthalein poly(ether ether ketone) (PEK‐C) /epoxy composite foams were prepared by free foaming process (Fre‐foams) and limited foaming process (Lim‐foams), respectively, and the effects of PEK‐C content and foaming methods on the cell structures, phase morphologies, and impact strength of epoxy foams were investigated. The results showed that the gas pressure in the bubbles promoted the resin curing process and polymerization‐induced phase separation process (PIPS) during the free foaming process, while the resin curing process and PIPS were highly constrained in Lim‐foams. The incorporation of PEK‐C in the Fre‐foams showed superior improvement in impact strength compared with the PEK‐C/epoxy Lim‐foams. By adding 12 wt% PEK‐C, the specific impact strength of Fre‐foams could be enhanced by 72%, and the improved specific impact strength was because the phase‐inverted structures could prevent crack initiation and propagation, and moreover the presence of PEK‐C led to significantly refine cell structure and reduce foam density. Interestingly, the impact strength of Lim‐foams was nearly independent on the PEK‐C content, it was attributed to the obviously increased cell size with increasing PEK‐C content, and also that the phase separation process was not carried out.